Operational Framework for Debt Sustainability Assessments in Low-Income Countries : Further Considerations. (Policy Papers; Policy Paper ;, 2005)
Building on initial discussions of the proposed framework in February/March 2004, and further considerations in September 2004, this paper responds to remaining concerns that need to be resolved to make the framework operational. These concerns relate to the indicative debt-burden thresholds (Section II); the interaction of the framework with the HIPC Initiative (Section III); and the modalities for Bank-Fund collaboration in deriving a common assessment of sustainability (Section IV). This note should be read in conjunction with the original proposal, which presented the wider issues on the use of the indicative thresholds, the evaluation of policies and institutions, and the need for discretion when assessing sustainability on a forward-looking basis.